2012
DOI: 10.1038/ijo.2012.78
|View full text |Cite
|
Sign up to set email alerts
|

Association of symptoms of attention-deficit/hyperactivity disorder with childhood overweight adjusted for confounding parental variables

Abstract: OBJECTIVE: There have been numerous reports on association between attention-deficit/hyperactivity disorder (ADHD) and overweight/obesity in children and adolescents; however, most studies adjusted only for a limited number of possible confounders. METHODS: We analyzed the data of 11 159 six through seventeen-year-old participants in the German Health Interview and Examination Survey for Children and Adolescents. We determined weight status based on measured anthropometry and national reference data by Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 63 publications
7
49
1
2
Order By: Relevance
“…13 14 However, the findings are inconsistent possibly because of cross-sectional designs, methodological and sample characteristic differences. [15][16][17] Some children with ADHD may have low self-esteem and social functioning problems as well as possible coordination difficulties. 18 19 These problems may influence self-confidence and participation in physical activity, referred to as exercise selfefficacy and could therefore become risk factors for the development of later obesity.…”
Section: Key Messagesmentioning
confidence: 99%
“…13 14 However, the findings are inconsistent possibly because of cross-sectional designs, methodological and sample characteristic differences. [15][16][17] Some children with ADHD may have low self-esteem and social functioning problems as well as possible coordination difficulties. 18 19 These problems may influence self-confidence and participation in physical activity, referred to as exercise selfefficacy and could therefore become risk factors for the development of later obesity.…”
Section: Key Messagesmentioning
confidence: 99%
“…The finding of effects in children was not echoed in the few studies confined only to preadolescent children in the literature,4 5 although with more data it may shade toward reliable. It remains possible, if not likely, that the effect reported by the present authors in children is primarily explained by effects of puberty.…”
Section: Limitationsmentioning
confidence: 84%
“…In a recent representative German community survey of 2,863 11- 17-year-old children and adolescents, overweight/obese minors were twice as likely to have an ADHD diagnosis, and youth with ADHD were twice as likely to be overweight or obese [15]. However, Egmond-Fröhlich et al [18] reported that in a German population sample of 11,159 8- to 17-year-old children and adolescents the association between obesity and ADHD symptoms as measured with the hyperactivity/inattention (HI) subscale of the SDQ was no longer significant after adjusting for family background variables.…”
Section: Introductionmentioning
confidence: 99%
“…Among the few epidemiological studies, three found an association between a diagnosis of ADHD or high rates of ADHD symptoms and obesity [13,14,15] while three did not find any association between ADHD symptoms measured by the Strengths and Difficulties Questionnaire (SDQ) and obesity [16,17,18]. In a recent representative German community survey of 2,863 11- 17-year-old children and adolescents, overweight/obese minors were twice as likely to have an ADHD diagnosis, and youth with ADHD were twice as likely to be overweight or obese [15].…”
Section: Introductionmentioning
confidence: 99%